EVALUASI SISTEM DRAINASE PADA AKSES JALAN PELABUHAN KENYAMUKAN SANGATTA KUTAI TIMUR - DEWI, INDAH SARI (KURVA S JURNAL MAHASISWA, 2018)
The path that I studied to make this thesis was one of the connecting road access to the comfort port, very east Kutai. The purpose of this research is to drain the air that occurs on the road surface from the tides of the sea water and rain that flows through existing drainage channels (existing) or that do not yet exist (none) directly to the sea. Therefore, it is necessary to make an air management system that happens, nothing can roll or direct to the existing channels. The current condition of the drainage network shows that it is less capable and optimal in flowing rain and air air from the tides of the sea well, because the drainage is still in the form of excavation from the excavator will not be able to install the sea or rain will damage the road conditions later. In its implementation, studies are needed in the existing dimensions, the furthest path length, concentration time, and current land use utilization. In analyzing secondary analysis, frequency analysis, measurement, planning and analysis. Rain gauge for return periods of 2, 5, 10 and 25 years respectively. After checking, it was found that the available capacity was not sufficient to accommodate the debit needed to repair the drainage system. One solution that can be applied is to create a new drainage channel